Educational Values of Taboo Expressions in the Sasak Speech Community: An Ethnography Study - Alhakimi, Dimas; Soepriyanti, Henny; Waluyo, Untung; Mahyuni, Mahyuni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This study aims to determine the form, meaning and perception of the community related to taboo things or expressions in Muncan Village. This research is an ethnography research using descriptive qualitative method design. The sample of this research is 10 people of Muncan Village from experts in culture to ordinary people. The data collection process in this research is by using observation and interview. In the process of analyzing the data is done by identifying, classifying, and explaining the meaning and perception of the community. The results of this study show that there are 57 taboos believed by the community. Therefore, it can be concluded that the people of Muncan Village still believe in many taboo things or expressions that they should not violate or do. In other words, taboo expressions and things in today's modern era are still believed to be things that should not be said or done in Muncan Village.